ANALISIS ALOKASI DANA ALOKASI KHUSUS FISIK BIDANG PERTANIAN DAN DANA ALOKASI KHUSUS PENUGASAN BIDANG IRIGASI - Robby Alexander Sirait (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
The aim of this research to analyze specific allocation funds of agriculture and irrigation. This study used secondary data, standard deviation and rating scale method. From this research, we found that allocations for specific allocation funds is not fully accurate to achieve the food security and food sovereignty. We reach to the conclusion based on our results that 32.28% of specific allocation funds is inaccurate.